Impacts of recent climate change on trends in baseflow and stormflow in United States watersheds. Issue 10 (27th May 2016) - Ficklin, Darren L.; Robeson, Scott M.; Knouft, Jason H.
Abstract: Characterizing the impacts of climatic change on hydrologic processes is critical for managing freshwater systems. Specifically, there is a need to evaluate how the two major components of streamflow, baseflow and stormflow, have responded to recent trends in climate. We derive baseflow and stormflow for 674 sites throughout the United States from 1980 to 2010 to examine their associations with precipitation, potential evapotranspiration, and maximum/minimum temperature. The northeastern (NE) and southwestern (SW) United States display consistent trends in baseflow and stormflow: increasing during fall and winter in the NE and decreasing during all seasons in the SW. Trends elsewhere and at other times of the year are more variable but still associated with changes in climate. Counter to expectations, baseflow and stormflow trends throughout the United States tend to change concurrently. These trends are primarily associated with precipitation trends, but increases in PET are influential and likely to become important in the future. Key Points: Northeastern U.S. increasing in baseflow and stormflow Southwestern U.S. decreasing in baseflow and stormflow Stormflow and baseflow changes largely from precipitation changes, but PET changes have also been influential